Analisis Semiotika Terapan terhadap Iklan YouTube “#CepetanGoSendInstant by Ariel NOAH x GoSend” - Arya Dwi Fatwa; Kurnia (UNISBA Press, 2023)
Abstract. In this journal applying semiotic analysis in the field of advertising is the study of the elements of advertising text and their relationships. Semiotic analysis in combination with experimental tools in the context of market research makes it possible to emphasize the effect of individual elements of advertising text on the customer, and not the effect of advertising as a whole, as was usually observed in previous researchers. This journal uses a qualitative method consisting of primary data and secondary data. The results of this study indicate that there is a correlation between the use of storylines in plots, the influence of advertising and consumer perceptions. The scale used can be applied to this advertising research, the combination of semiotic analysis and experimental methods presented in this study allows researchers to get deeper into advertising content in relation to advertising effectiveness. The results can also advance understanding of the impact of ad text elements on users in future theoretical and practical research. Abstrak. Dalam jurnal ini menerapkan analisis semiotik dalam bidang periklanan adalah kajian tentang unsur-unsur teks iklan dan hubungannya. Analisis semiotik yang dikombinasikan dengan alat eksperimental dalam konteks riset pasar memungkinkan untuk menekankan efek elemen individual dari teks iklan pada pelanggan, dan bukan efek iklan secara keseluruhan, seperti yang biasanya diamati dalam peneliti sebelumnya. Jurnal ini menggunakan metode kualitatif yang terdiri dari data primer dan data sekunder. Hasil penelitian ini menunjukkan bahwa ada korelasi antara penggunaan alur cerita dalam plot, pengaruh iklan dan persepsi konsumen. Skala yang digunakan dapat diterapkan pada penelitian periklanan ini, kombinasi analisis semiotik dan metode eksperimental yang disajikan dalam penelitian ini memungkinkan peneliti untuk lebih dalam tentang konten iklan dalam kaitannya dengan efektivitas periklanan. Hasilnya juga dapat memajukan pemahaman tentang dampak elemen teks iklan pada pengguna dalam penelitian teoretis dan praktis di masa mendatang.